434 An in-vehicle technology intervention to improve safe driving in high-risk teens. (20th November 2022) - Yang, Jingzhen (Ginger); Hamann, Cara; Kaur, Archana; Feiss, Robyn; Roth, Lisa; Zhou, Motao; Peek-Asa, Corinne
Abstract : Context: Motor vehicle collisions are the leading cause of death among teenagers. Teen drivers who have committed a traffic violation are at even greater risk. In-vehicle feedback technology helps improve driving behaviors. However, programs using this technology to actively engage parents in promoting safe teen driving practices are scarce. Process: We enrolled teen drivers (ages 16–17) cited for a traffic violation, along with a parent/guardian, following their mandatory court appearance. Dyads were randomized into three groups: 1) Control; 2) Device feedback to teens only; or 3) Device feedback to both teens and parents; parents also received individualized virtual training with a traffic safety communication specialist. We installed commercially available in-vehicle feedback devices in the teens' cars, along with apps on their phones. We used an in-vehicle device and an app to collect driving data that were shared with teens and parents to help increase parents' communication with their teens about their safe driving practices. Analysis: We assessed risky driving events (hard braking, sudden acceleration) and unsafe driving behaviors (speeding, no seatbelt use) per 1, 000 miles driven, and frequency of distracted driving and recidivism in teen drivers across the three study groups. Outcomes: Study outcomes will identify the effectiveness of in-vehicle technology comparing rates of risky driving events and unsafe behaviors among the two intervention groups (with and without parent training) to the control, and the two intervention groups to each other. Learning Outcomes: Explain the effects of interventions targeting teen drivers using in-vehicle technology augmented with parent communication training.